Desenvolvimento de um dispositivo para avaliação de geração de tensões em soldagem - Almeida, Daniel de (2000)
One of the largest problems in welding operations is the generation of thermal stress that appears in the form of residual stress, deformation or even joint collapse. This fact is due to the source of heat used to melt or to coalesce the metais, what implicates in a thermal diffusion for all directions. Consequently, during the welding, thermal expansions and contractions happen in the heated areas, and part of them is restrained by the cold parts, generating in a complex stress field during cooling. To minimize the generation of stress, the use of appropriate procedures (techniques and parameters) is demanded. The evaluation of the induced stress in welded joints is usually a complex process and highly cost, for involving specialized personnel and specific equipment. A viable solution, however, could be the simulation of the induced stress in proof specimens. To try overcoming the problem of stress evaluation in welded joints, in this work was proposed to develop a simple and economical device to measure the leveis of stress induced in welded joints, working with proof specimens of small dimensions. Such a device seeks to evaluate the efficiency of several techniques applied in practice for reduction of thermal stress, techniques that are usually applied in maintenance welding. The developed device is a “sensor bar” for both tension/compression and bending efforts, in which is possible to determine the resultant induced stress in a real welded specimens placed under movement restriction. The device was initially calibrated through static loading by placing a load-cell in the place of the specimens and by comparing the reading of the sensor with the ones from the cell. During this phase and in preliminary tests there was the need of redesigning geometrically the bar to avoid reading instability. After re-calibration, the sensor was evaluated through two welding procedures. The first one used variation of the pre-heating temperature in the welding of root passes and the second one employed variation of the number of passes to fill out the same volume of welds. A misbehavior of the bending stress in relation to the expected values was verified and, through Finite Element Analysis, the results were justified. The obtained results demonstrate that the device has enough sensibility to differentiate leveis of generated tensions in each case.